2011
DOI: 10.1002/cvde.201004300
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometry of Nickel Oxide Films Prepared by ALD

Abstract: Nickel oxide films obtained from nickelocene and ozone by atomic layer deposition at 230°C are substoichiometric, but have the crystal structure of NiO. Oxygen can be driven out of the solid by annealing under inert atmosphere, or added into it via aerobic annealing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 14 publications
3
43
1
Order By: Relevance
“…These are relatively long saturation times compared to other processes performed in this reactor, [ 43,44 ] perhaps refl ecting slow kinetics of the Ni(Cp) 2 on the surface. Bachmann et al also used a relatively long Ni(Cp) 2 pulse of 2 s compared to an O 3 pulse of just 0.2 s [ 41 ] and Lu et al used a Ni(Cp) 2 pulse time of 7 s for their process. [ 37 ] The thickness measured as a function of number of cycles under saturation conditions is shown in Figure 1 c. The steady state growth rate is 0.63 Å cycle −1 and there is a nucleation delay of ≈20 cycles on O 3 -cleaned Si.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…These are relatively long saturation times compared to other processes performed in this reactor, [ 43,44 ] perhaps refl ecting slow kinetics of the Ni(Cp) 2 on the surface. Bachmann et al also used a relatively long Ni(Cp) 2 pulse of 2 s compared to an O 3 pulse of just 0.2 s [ 41 ] and Lu et al used a Ni(Cp) 2 pulse time of 7 s for their process. [ 37 ] The thickness measured as a function of number of cycles under saturation conditions is shown in Figure 1 c. The steady state growth rate is 0.63 Å cycle −1 and there is a nucleation delay of ≈20 cycles on O 3 -cleaned Si.…”
Section: Resultsmentioning
confidence: 98%
“…Because of discrepancies in previous reports of this NiO ALD process, we performed a systematic characterization of the ALD deposition. [ 37,41,42 ] NiO was deposited at a stage temperature of 275 °C and a Ni(Cp) 2 bubbler temperature of 85-90 °C. Under these conditions, measurements of fi lm thickness after 75 cycles for different pulse lengths showed that saturation was achieved after ≈8 s for the Ni(Cp) 2 pulse and ≈3 s for the O 3 pulse as seen in Figure 1 a,b.…”
Section: Resultsmentioning
confidence: 99%
“…Such a large variation in temperatures is due to the technological differences in the device ALD setups. There are different types of reagent containers such as open source boats [29,36], stainless-steel bottles [61], and stainless-steel bubblers [47], which differ in their construction. Depending on the type of the container, the requirements for the reagent vapor pressure are different.…”
Section: Atomic Layer Deposition Of Nio Thin Filmsmentioning
confidence: 99%
“…In this work, for the NiCp 2 and Ni(MeCp) 2 storage and pulse, we used stainless-steel bottles, which require the highest temperature of over 100 • C [60,61]. We selected 90 • C as the first temperature of the container.…”
Section: Atomic Layer Deposition Of Nio Thin Filmsmentioning
confidence: 99%
“…Therefore the development of sensors that are tough small size, long lifetime, and quick in response and with sufficient sensitivity for the detection of nitrogen dioxide in low concentrations, in the environment is so important and needed. The surface morphology and particle size is the key variables in the sensing properties of Metal oxide gas sensors and are mostly organized by the adsorbed oxygen molecules, obviously increasing the surface-tovolume ratio or enhancing the surface adsorption which will increase the resistance change and improve the sensitivity [33]. It is known for many years that the adsorption-dependent electrical properties of metal oxide semiconductors are often sensitive to much gaseous ambient.…”
Section: Gas Sensing Propertiesmentioning
confidence: 99%